(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Lexicology, as a branch of linguistics, focuses on the study of words, their meanings, structures, and relationships within a language. While essential for understanding linguistic systems and language evolution, lexicology encounters several challenges. These include defining the concept of a “word,” addressing polysemy and homonymy, managing synonymy and antonymy, understanding word formation processes, and adapting to the rapid changes in vocabulary due to societal and technological progress. This article explores these problems, highlighting their implications for linguistics and practical applications in lexicography, translation, and language education